FORMULATION AND EVALUATION OF BILAYERED FLOATING TABLET OF DILTIAZEM DRUG - Makwana, Priti K; Rathva, Sunil R; Chauhan, Nimisha P; Patel, Krishna B; Brahmbhatt, Hiral B; Jain, Hitesh N; Upadhyay, Umesh M (Journal of Drug Delivery and Therapeutics, 2014)
Aim of study was to develop bilayered floating drug delivery for treatment of hypertension by delivering loading and maintenance dose for fast achievement of peak plasma concentration and maintaining the same respectively. The prepared drug loaded bilayered floating tablets were evaluated for pre and post compression parameters. Stability study of the promising formulation was also performed. The tablets were prepared by direct compression method. The loading dose was delivered in the form of immediate release layer prepared by different super-disintegrations and maintenance dose was delivered through sustained release layer prepared by using polymers like HPMC K15M and Carbopol 934P. Both the immediate release layer and sustained release layers were separately optimized and then combined to optimize the bilayered floating tablets. No interactions were found between drug and excipients. Formulation containing crosscarmellose sodium shows immediate drug release. Formulation Containing HPMC K15M shows sustained release action and bilayered formulations FB7 shows releases up to 12 hours with good buoyancy and total floating time. All the Bilayered floating formulations buoyant up to 12 hrs. Bilayered floating tablets with release characteristics offer critical advantages such as, site specificity with improved absorption and efficacy. This technology can be inculcated to various medicaments which have stomach as the major site of absorption. Key words: Diltiazem, Bilayered floating tablet, sustain release tablet